The first discovery of Hypsodontus (Artiodactyla, Bovidae) from the Early Miocene of Linxia Basin, Gansu Province, China - Yu-Qing Jin; Qigao Jiangzuo; Shi-Qi Wang (Fossil Record)
Hypsodontinae is a highly specialized subfamily of Bovidae, primarily distributed across East and West Asia as well as Eastern Europe during the Miocene; however, the type genus Hypsodontus had not been documented in East Asia. Here, we report a new species of Hypsodontus, Hypsodontus sinensis sp. nov., from the Dongxiang Formation at the Citan locality, Linxia Basin, China, dating to the late Early Miocene (~17.2 Ma). This marks the first definitive record of the type genus in China. The new material consists of a horn core that exhibits more than 1/3 circle of strong homonymous twisting, uniform elongation, and a smooth surface, displaying closer affinities to H. pronaticornis. The age of Hypsodontus sinensis sp. nov. represents the oldest known record, suggesting that this genus might have originated in China and radiated during the late Early Miocene or early Middle Miocene. The evolutionary relationships among the members of Hypsodontinae, i.e., Hypsodontus, Kubanotragus, and Turcocerus, are also discussed here. Materials from the Xishuigou locality and the Halamagai Formation of the Junggar Basin may represent an ancestral form of these genera mentioned above, possibly an early variant of Kubanotragus. The discovery of this new species at the Citan locality illustrates an early diversification of Hypsodontus in China and provides critical insights into the early evolution of Bovidae.